FROZEN 2 : THE HERO’S JOURNEY FROM THE MYTHOLOGY TO THE MOVIES WITH FOLKLORISTIC OVERVIEW - Chaiklam, Sukunyasopee (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2021)
The hero’s journey from the mythology to the movies with folkloristic overview has found that Frozen 2 is presented in line with the complete, twelve steps in which Christopher Vogler draws on Joseph Campbell’s theory of “The Hero’s Journey” to analyze the present popularity of screenwriting. The information in the story also indicates that the author was inspired by many parts of mythology including the Fifth Spirit as a bridge connecting humans with the forces of nature, etc. Moreover, the storyline with the adventures of heroes in mythology and information taken from it for the benefit of presentation is part of the transformation of the mythological narrative to the presentation of the story through the movie. Though the mythology is still incomplete in essence, the movie purposive conveyance is apparent to show us not merely courageous acts but also the sacrifice for the common good that guides the spiritual development of humankind to lead us on our journey toward the ultimate goal in life.